Employee perceptions on safety and working conditions in the Textile industry: A comparison between Spinning and weaving units. - Gopalsamy Selvaraj, Murali Manohar (2012)
Indian textiles contribute to 3.5-4% of the textile exports in the world market. Indian textile industry is one of the leading textile industries in the world and second largest industry in India after agricultural industry. Textile industry of India has started shifting from the unorganised to organised business culture after the economic liberalization in the early 90’s. Textile industry in India provides employment to 35 million people directly and indirectly and being the largest foreign exchange revenue generating sector in the country. The industry being highly labour intensive the need for the textile organisations to retain their labour is highly important in recent days. Working conditions and safety measures being important aspect of the workplace and the need for concentration in these aspects is very much higher for the textile organisations to retain their workforce. In our research employee’s perceptions are obtained to develop and enhance the working conditions and safety measures in the textile units. The study was limited to spinning and weaving units rather than all of the individual components of textile industry. The employees perceptions are obtained through the form of the questionnaires and the obtained data are analysed using statistical tool SPSS. The total number of research participants was 194 employees from six spinning and four weaving units. The statistical methods of hierarchical multiple regressions are used to understand the relationship and impact of working conditions on job satisfaction, burnout and stress levels in employees. The impact of safety measures on the job satisfaction are analysed with a more focus into the nine safety dimensions in the spinning and weaving sector. The results show that working conditions has an impact on the job satisfaction, burnout and stress in employees. The safety measures were found contributing to the employee job satisfaction in the entire textile industry. The safety dimensions of ‘Personal appreciation of risk’ and ‘safety rules and procedures’ post a lower scores in the spinning and weaving sector respectively when compared to the other safety dimensions.